Workplace Gains beyond the Wagner Act: The New York Taxi Workers Alliance and Participation in Administrative Rulemaking. (June 2018) - Johnston, Hannah
Workers in traditional employment relationships have long relied on unionization and collective bargaining to counter unequal power relationships in the workplace and improve the terms and conditions of their work. Within the North American context, however, workers in select industries or with select employment status are legally excluded from this paradigm and unable to access basic labor law protections. This article examines historic gains made by the New York Taxi Workers Alliance to improve the work experience of yellow cab drivers through collective participation in the City of New York's Administrative Rulemaking process. Exploring examples, including the 2003/2004 meter increase, Driver's Bill of Rights, and the Drivers' Benefit Fund, I argue that in the absence of a collective bargaining agreement, administrative rulemaking can provide both a site for negotiation about the content and structure of work, and can be employed to uphold the rights and gains made through workers' collective action.